2013
DOI: 10.1007/s00442-013-2620-0
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of species-specific perfume blends: influence of habitat-dependent compound availability on odour choices of male orchid bees (Euglossa spp.)

Abstract: Male orchid bees (Euglossini, Apidae, Hymenoptera) expose species-specific blends of volatile chemicals (perfume bouquets) during their courtship display. The perfumes are acquired by collecting fragrant substances from environmental sources, which are then accumulated in specialised hind leg pouches. To balance the perfume composition, the males need to find and collect the required substances in specific relative amounts while facing seasonal, local or habitat-dependent differences in compound availability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…) and similarity to the species centroid increases with the number of compounds included (Pokorny et al . ). Additionally, because within‐species variability is required for sexual selection to act on male traits (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…) and similarity to the species centroid increases with the number of compounds included (Pokorny et al . ). Additionally, because within‐species variability is required for sexual selection to act on male traits (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Species-specific preferences for collecting certain compounds are evident (Ackerman, 1989), resulting in distinct tibial blends (Eltz et al, 2005a). There is, however, broad overlap in the range of chemicals collected by different species (Ackerman, 1983a;Janzen et al, 1982;Pearson and Dressler, 1985) as well as geographical and seasonal shifts of preferences (Ackerman, 1989;Pokorny et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This finding reinforces the idea that Euglossini are generalists regarding the available source (floral or non-floral source), but some species may be specialists regarding the kind of perfume they are attracted to or forage. Recently, Pokorny et al (2013) reported by means of perfume attraction assays that two species of Euglossa reacted differently to specific extract compounds. The experiments showed that only co-specific males were attracted when those volatiles were offered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cappellari et al (2009) included the family Plantaginaceae in the group of scent flowers visited by the male orchid bees. Other aromatic sources reported as perfume attractants for the Euglossini include tree trunks (Rebêlo and Garófalo 1991), rotting wood (Whitten et al 1993), roots (Ramírez et al 2002), fungi (Pearson and Dressler 1985;Cappellari and Harter-Marques 2010), leaf surfaces (Pemberton and Wheeler 2006) and also the hind leg of conspecific males (Carvalho Filho 2010, Pokorny et al 2013.…”
Section: Introductionmentioning
confidence: 99%